Cytocompatibility and antimicrobial efficacy of pluronic F-127 coated colloidal silver nanoparticles as an endodontic irrigant - M S Rama Rao; Sai Harshini Pindiprolu; Mahendra Varma Nadimpalli; Sudhakar Naidu; Gowtam Dev Dondapati; T BV G Raju (Wolters Kluwer Medknow Publications, 2019)
Aim and objective: The aim and objective of present study are to prepare and characterize Pluronic F-127 coated colloidal silver nanoparticles and to evaluate its cytocompatibility and anti-microbial efficacy in comparison to 5.25% NaOCl. Materials and Methodology: The cytocompatibility was evaluated on L929 human fibroblast cell line by MTT assay at five different concentrations of Pluronic F-127 coated colloidal silver nanoparticles [0.01μg/mL; 0.1μg/mL; 1μg/mL; 10μg/mL; 100μg/mL] and antimicrobial activity was evaluated by Agar well diffusion method on Enterococcus faecalis (ATCC 29212) using 100μL Pluronic F-127 coated colloidal silver nanoparticles [as test solution], 100μL 5.25%NaOCl [as standard solution], 100μL water [as control]. Statistical Analysis: Statistical analysis was performed using one way analysis of variance (ANOVA), followed by Dunnett's multiple comparison test (Graph Pad Prism, Version 6, Graph Pad Software Inc., La Jolla, USA). Results: The values with p < 0.05 were considered significant. MTT assay showed Pluronic F-127 coated colloidal silver nanoparticles are more cytocompatible on healthy fibroblast cells. In antimicrobial activity there is more significant difference among groups. Conclusion: Pluronic F-127 coated colloidal silver nanoparticles showed more zone of inhibition compared to NaOCl. Pluronic F-127 coated colloidal silver nanoparticles proved to be more cytocompatible and has highest antimicrobial activity compared to NaOCl.